2007
DOI: 10.1007/bf03022777
|View full text |Cite
|
Sign up to set email alerts
|

Case series: The McGrath® videolaryngoscope — an initial clinical evaluation

Abstract: Purpose: To document tracheal intubation success rates and airway instrumentation times using the newly designed McGrath® videolaryngoscope. Methods:We prospectively recorded factors associated with difficult tracheal intubation, factors causing actual difficulty in tracheal intubation, as well as complications arising from use of the new McGrath® videolaryngoscope in a series of adult patients with normal preoperative airway examinations. All patients were undergoing scheduled or elective surgery. In the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 32 publications
(40 reference statements)
5
100
1
4
Order By: Relevance
“…The use of a gum-elastic bougie, a common adjunct to difficult tracheal intubations, was left to the preference of the anaesthetist [17]. The videolaryngoscope blade was inserted along the midline of the tongue, and a styletted tracheal tube angulated according to the curve of the videolaryngoscope blade was introduced as suggested by the product information and a previous case series [18,19]. If more than one intubation attempt was required, the patient received bag-andmask ventilation between attempts and various manoeuvres were employed, including external laryngeal pressure, readjustment of the stylet and use of a bougie.…”
Section: Methodsmentioning
confidence: 99%
“…The use of a gum-elastic bougie, a common adjunct to difficult tracheal intubations, was left to the preference of the anaesthetist [17]. The videolaryngoscope blade was inserted along the midline of the tongue, and a styletted tracheal tube angulated according to the curve of the videolaryngoscope blade was introduced as suggested by the product information and a previous case series [18,19]. If more than one intubation attempt was required, the patient received bag-andmask ventilation between attempts and various manoeuvres were employed, including external laryngeal pressure, readjustment of the stylet and use of a bougie.…”
Section: Methodsmentioning
confidence: 99%
“…The McGrath Ò videolaryngoscope (Aircraft Medical, Edinburgh, Scotland) is a novel, portable videolaryngoscope that provides excellent laryngoscopic views in patients with normal airways [17], and in patients in whom direct laryngoscopy has been difficult or has failed [18]. Information about its use by novice practitioners is limited [9].…”
mentioning
confidence: 99%
“…The present study revealed an intubation time of 47. among studies (6,9,12). While conducting an orotracheal intubation with the McGrath video laryngoscope, a stylet has to be used for the orotracheal tube.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various studies and case reports have demonstrated that the McGrath Series 5 video laryngoscope has several advantages, such as improved view of the glottis, low incidence of injury, and ease of use as an alternative to direct laryngoscopy (5,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation